The Impact of Climate Change on the Economics of Dairy Farming - a Review and Evaluation - Maria Martinsohn; Heiko Hansen (German Journal of Agricultural Economics (GJAE), 2012)
The impact of climate change has become a major concern within the agricultural profession. While many studies on Climate Change Impact Assessment (CCIA) deal with crop farming, little has been done with regard to livestock farming. This paper aims to shed light on the present state of research in the field of dairy farming, one of the major sectors in agriculture, in a three-fold manner. First, potential climate change impacts in dairy farming are discussed qualitatively. Second, challenges and methodological approaches in economic CCIA are presented, with a closer look at the issue of climate data and farm-level adaptation. Third, an overview and assessment of available studies on economic CCIA in dairy farming along a set of evaluation criteria is provided. The paper concludes with further research opportunities in this field.
Keywords: 330; Klimawandel; Wirtschaftliche Anpassung; Milchviehhaltung